Pengelolaan Administrasi Madrasah Tsanawiyah Negeri Dalam Meningkatkan Kualitas Pendidikan Madrasah - Kristiawan, Muhammad; Asvio, Nova (Universitas Kristen Satya Wacana, 2018)
This research aimed at exploring the management of administration in MTs Negeri Padang Panjang in upgrading the Madrasah quality. This research was qualitative. Data collection used documentation study and in-depth intervie. The results obtained indicate that the management of administration in MTs Negeri Padang Panjang was run well in upgrading the quality of Madrasah. The quality of management administration was seen from the administration of studentsâ recruitment, curriculum, educators and staff, and counseling. This research implicates to supervisors and Madrasah in West Sumatera to learn the management of administration in MTs Negeri Padang Panjang in upgrading the Madrasah quality.